The Arctic lithosphere: Thermo-mechanical structure and effective elastic thickness - Struijk, Erzsébet L. M.; Tesauro, Magdala; Lebedeva-Ivanova, Nina N.; Gaina, Carmen; Beekman, Fred; Cloetingh, Sierd A. P. L. (Global and Planetary Change, 2018)
For the first time, lithospheric temperatures, strength, and effective elastic thickness (Te) distributions are estimated for the Arctic region north of 68°. To this aim, we use ArcCRUST, a recent model of the Arctic crust, which includes the thickness and density of the crust and sediments, the boundaries between the continental and oceanic crust, and the age of the oceanic lithosphere. We estimate the temperature variations in the continental lithosphere assuming steady-state conditions, for a constant surface heat flow of 50 mWm−2 and 62 mWm−2 for the onshore and offshore regions, respectively. In the oceanic domain, the temperature variations are estimated adopting a global depth and heat flow model. We discuss the robustness of the results by comparing the new thermal field with temperatures obtained from inversion of a regional seismic velocity model. The results are used as input for estimating integrated strength and Te, assuming a mafic crustal rheology. Our models predict a sharp transition between cratonic areas, characterized by high strength and Te, and tectonically active areas with a weaker lithosphere, corresponding to the continental shelves and the oceanic spreading ridges. The significant lateral change in our modeled strength and Te at the edges of Greenland and Canadian Arctic and along the active mid-ocean ridge in the NE Atlantic corresponds to increased observed seismic activity.